Comparing the Postoperative Analgesic Efficacy of Preemptive Ketamine with Intraperitoneal Ropivacaine Combination in Patients Undergoing Laparoscopic Colecystectomy under General Anesthesia - Özyılmaz, Mehmet Ali; Ölmez, Gönül; Şimşek, Edip (Fırat University, 2006)
Objectives: In this study, the postoperative analgesia efficacy of giving intravenous ketamine or intraperitoneal injection of ropivacaine alone or in combination to the patients on whom laparoscopic cholecystectomy was aimed to investigate. Materials and Methods: Forty-five patients of ASA I-II classification were included in the study. Patients were randomized to 3 groups. Following standard general anesthesia induction, Group I received 1 mg/kg ketamine intravenous and after pneumoperitoneum was formed, 40 ml saline solution was given intraperitoenally. Group II received ketamine 1 mg/kg and 40 ml ropivacaine 0.25% (100 mg) were given intraperitoenally. Group III received IV saline and intraperitoenally 40 ml ropivacaine 0.25% in the same manner. The postoperative pain of the patients was assessed using visual analogue scale (VAS). The VAS score of the patients at the 0, 30 min, 2, 4, 6, 12, 24 hours and total morphine requirements (TMR) at 24 hour were compared. Results: VAS scores in Group II and III were found to be lower than that of Group I in all time measurements (p

Amaç: Çalışmamızda, laparoskopik kolesistektomi uygulanan hastalara intravenöz ketamin verilmesinin ve/veya intraperitoneal ropivakain uygulanmasının postoperatif analjezik etkinliğinin araştırılması planlandı. Gereç ve Yöntem: ASA I-II grubu 45 hasta çalışmaya dahil edildi. Hastalar randomize olarak 3 gruba ayrıldılar. Standart genel anestezi uygulamasını takiben Grup-I'e; 1 mg/kg ketamin iv olarak uygulandı ve pnömoperitoneum oluşturulduktan sonra sonra 40 ml salin solüsyonu plasebo amacıyla intraperitoneal olarak uygulandı. Grup-II'ye; 1 mg/ kg ketamin iv olarak uygulandı ve 40 ml %0.25'lik ropivakain (100 mg) solüsyonu intraperitoneal olarak uygulandı. Grup-III'e ise; intravenöz salin ve 40 ml %0.25'lik ropivakain (100 mg) solüsyonu benzer şekilde uygulandı. Postoperatif analjezi, hasta kontrollü iv morfinle sağlandı. Hastaların ağrı düzeyleri görsel analog skala (VAS) ile belirlendi. Grupların 0, 30 dk, 1, 2, 4, 6, 12, 24. saatlerdeki VAS skorları ile 24 saatlik total morfin tüketim (TMT) miktarları karşılaştırıldı. Bulgular: Postoperatif ağrı skorlar karşılaştırıldığında takip edilen tüm zaman birimlerinde gruplar arasında istatistiksel olarak anlamlılık vardı. Grupların ikili karşılaştırılmasında II. ve III. Gruplardaki VAS skorları, I. Gruba göre tüm zaman birimlerinde istatistiksel olarak anlamlı derecede düşük bulundu (p
Laparoskopik Kolesistektomilerde Genel Anestezi Altında Preemptif Ketamin ile İntraperitoneal Ropivakain Kombinasyonunun Postoperatif Analjezik Etkinliklerinin Karşılaştırılması